Pengaruh Persepsi Harga, Promosi Penjualan Dan Citra Merek Terhadap Kepuasan Pelanggan Di Warung Omah Bumbu Ireng - Putra, Novan Satria; Wahono, Budi; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine the effect of perceptions of promotional and sales prices and brand image on customer satisfaction at the Omah Spices Ireng shop. The data used in this study uses primary data by distributing questionnaires to respondents. The population and sample of this research are the customers of Ireng Spice House. The research sample was taken from the population using a sampling technique in the form of a purposive sampling method with sample measurements using the Malhotra method. The results obtained using the multiple linear regression test Y = -8.665+0.803X1 +0.088 X2 + 0.622X3 +e, and the research tests used the f test and t test. The results of this study indicate that partially the price perception and brand image variables have a positive effect on customer satisfaction at Warung Omah Bumbu Ireng while sales promotion variables have no significant effect on customer satisfaction at Warung Omah Bumbu Ireng. While simultaneously the perception of price, sales promotion and brand image together have a positive effect on customer satisfaction at Warung Omah Bumbu Ireng. Keywords: Perceived Price, Sales Promotion, Brand Image and Customer Satisfaction